2006
DOI: 10.1103/physrevb.74.113106
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous temperature dependence of the single-particle spectrum in the organic conductor TTF-TCNQ

Abstract: The angle-resolved photoemission spectrum of the organic conductor TTF-TCNQ exhibits an unusual transfer of spectral weight over a wide energy range for temperatures 60K < T < 260K. In order to investigate the origin of this finding, here we report numerical results on the single-particle spectral weight A(k, ω) for the one-dimensional (1D) Hubbard model and, in addition, for the 1D extended Hubbard and the 1D Hubbard-Holstein models. Comparisons with the photoemission data suggest that the 1D Hubbard model is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…This questions the assumption of a surface relaxation and hence an enhanced value of t to explain the experimental data. Results by exact diagonalization 6 for T = 0 found that the inclusion of the nearest-neighbor Coulomb repulsion V in the extended HM offers a possible loop hole since it effectively increases the band widths of the spinon and holon excitations to match the experimental dispersions while, at the same time, allowing for a smaller t and hence a smaller J ef f in better agreement with experiment. Indeed, Cano-Cortés et al 5 recently have reported on density-functional results which find that the long-ranged Coulomb repulsion even to the third nearest neighboring molecule within a stack is still about 20% of U.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This questions the assumption of a surface relaxation and hence an enhanced value of t to explain the experimental data. Results by exact diagonalization 6 for T = 0 found that the inclusion of the nearest-neighbor Coulomb repulsion V in the extended HM offers a possible loop hole since it effectively increases the band widths of the spinon and holon excitations to match the experimental dispersions while, at the same time, allowing for a smaller t and hence a smaller J ef f in better agreement with experiment. Indeed, Cano-Cortés et al 5 recently have reported on density-functional results which find that the long-ranged Coulomb repulsion even to the third nearest neighboring molecule within a stack is still about 20% of U.…”
Section: Discussionsupporting
confidence: 63%
“…3,4 On the other hand, further theoretical work has shown that the also observed transfer of spectral weight at k F over the entire conduction band width with increasing temperatures cannot be reconciled within this parameter set. 6,20 The effective magnetic exchange J ef f which defines a characteristic temperature for the onset of such an spectral-weight transfer would come out much too large within the 1D HM. This questions the assumption of a surface relaxation and hence an enhanced value of t to explain the experimental data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature dependence in the Luther-Emery phase interestingly shows that above the temperature scale at which the single gap opens at the Fermi energy, features of the Luttinger liquid phase, namely a polaronic band crossing the Fermi energy and a gaped charge mode, are apparent. This observation should be set in the context of photoemission experiments carried out on TTF-TCNQ organics where measurements are carried out at a temperature scale above the Peierls transition and interpreted in terms of a Luttinger liquid model [1,3,4,5]. For the Holstein model given by Eq.…”
Section: Discussionmentioning
confidence: 99%
“…One can mention the quasi one-dimensional organics TTF-TCNQ where photoemission experiments are carried out down to 60 K just above the Peierls transition [1]. A detailed modeling of this experimental situation is bound to include both electronic correlations [2,3,4,5] as well as the phonon degrees of freedom [6]. In two dimensions the electron-phonon interactions leads to a delicate interplay of superconductivity and charge density waves depending on the partial nesting properties of the Fermi surface [7,8].…”
Section: Introductionmentioning
confidence: 99%